The Development of Morality and Ethics in Student Volunteers by Teamwork Activities in the Technical Secretary Course - Spiller, Pawina (ASEAN Journal of Education, 2019)
The purpose of this research was to study the ethical behaviour and the development of ethics in volunteer students through teamwork activities. The test students were 38 students who were enrolled in the technical secretary course. The research instrument was a questionnaire with a reliability of 0.97. Statistics used in the study were the frequency, percentage, average and standard deviation. The findings were: 1) The majority of the sample, 92.11 percent, was girls. They participated in group activities 5-8 times, which accounted for 44.74 percent. 2) The students were evaluated by measuring the percentage of ethical behaviours. Overall it increased from 36.18 percent to 55.48 percent after participating in the program. It was found that the ethical behaviour of the volunteers, students of the technical secretary course, overall was = 3.67. When considering individual items, it was found that they would help those inferior, in the overall highest level = 4.24. And when considering students’ behaviour, ethics and volunteerism were on the high level; the students would devote their time to helping others. Also they participated to benefit social development and tried to help the others as soon as possible. The groups were willing to work for the public, although they were disadvantaging themselves. They paid attention to the problems of society with enthusiasm, and were generous and kind to others. They sacrificed their time to provide social services willingly and behaved as good examples to others as well, especially to students who volunteered only at a moderate level. The students volunteered to work for others without expecting anything in return, because they wanted to develop a better society.